METHODOLOGY OF TEACHING SPORTS GAMES - Madaminov Oribdjan Nishanbayevich (Proximus Journal Publishing, 2025)
The higher state educational standard requires students to be a specialist in the field of physical culture (bachelor) with knowledge and socio-economic sciences: understanding the role of physical culture in human development and professional training; to have a system of practical skills and abilities that ensure preservation and strengthening of health, development and improvement of psychophysical abilities, qualities, self-determination in physical culture; it should include features such as gaining experience to achieve life and professional goals. "Sports Games and Methods of Teaching It". It can be used by students of physical education, masters and physical education teachers of secondary schools, coaches of primary training groups of basketball, volleyball, football and handball players of sports schools, organizers-instructors in physical education and all fans of these sports games.
Keywords: Basketball; volleyball; football and handball